A family screening of CD19 gene mutation by PCR-RFLP - Karaselek, Mehmet Ali; Kapaklı, Hasan; Güner, Şükrü Nail; Kurar, Ercan; Küççüktürk, Serkan; Keleş, Sevgi; Reisli, İsmail (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Mutation(s) in the gene encoding the CD19 molecule affect CD19 protein expression and primary immunodeficiency (PID) occurs. The PCR-RFLP method, which is faster and cheaper than other mutation detection methods, is rarely used in the diagnosis of PID. The study aimed to genetically identify CD19 deficiency, which is a PID, using the PCR-RFLP method. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. A total of 8 patients and two healthy controls were included in the study and the relevant region genotypes in the CD19 gene were determined by performing PCR-RFLP analysis. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The index case, newborn baby and mother were also included in the study. It was determined that the index case (P6) was homozygous mutant, the newborn baby (P7) and mother (P8) had heterozygous genotype. Based on this situation, one child (P1) was found to be homozygous mutant, mother (P2), father (P3) and other children (P4 and P5) had heterozygous genotype in the family, which was determined to be related to the first case. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. In our study, it has been shown that PCR-RFLP is a method that can be used in the diagnosis of PID by determining genotypes using PCR-RFLP, and especially in terms of rapid genetic testing of family screenings.